2015
DOI: 10.1016/j.nicl.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Usage of fMRI for pre-surgical planning in brain tumor and vascular lesion patients: Task and statistical threshold effects on language lateralization

Abstract: Background and purposeFunctional magnetic resonance imaging (fMRI) is a non-invasive pre-surgical tool used to assess localization and lateralization of language function in brain tumor and vascular lesion patients in order to guide neurosurgeons as they devise a surgical approach to treat these lesions. We investigated the effect of varying the statistical thresholds as well as the type of language tasks on functional activation patterns and language lateralization. We hypothesized that language lateralizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…Due to the denominator term (LI1 + LI2), cases where LI's are of opposite signs, have larger variability in LI. Our current study found that LI VAR has a task‐dependence, similar to the findings by Nadkarni et al () who explored laterality within expressive versus receptive language tasks. Similarly, our study suggests that LI variability has a threshold‐dependence which is similar to the findings by Ruff et al ().…”
Section: Discussionsupporting
confidence: 90%
“…Due to the denominator term (LI1 + LI2), cases where LI's are of opposite signs, have larger variability in LI. Our current study found that LI VAR has a task‐dependence, similar to the findings by Nadkarni et al () who explored laterality within expressive versus receptive language tasks. Similarly, our study suggests that LI variability has a threshold‐dependence which is similar to the findings by Ruff et al ().…”
Section: Discussionsupporting
confidence: 90%
“…fMRI can be used to for sensory motor, language, and memory mapping—all of which have important implications for presurgical planning and intraoperative navigation. 9597 …”
Section: Presurgical Planning Techniquesmentioning
confidence: 99%
“…Multiple studies have documented the dependence of the LI obtained on the threshold chosen (Rutten et al, 2002; Adcock et al, 2003; Seghier et al, 2004; Abbott et al, 2010; Nadkarni et al, 2015). As illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%